Zdravljenje z zdravili, urejenost bolezni in kakovost življenja bolnikov z astmo in KOPB v Sloveniji - Janežič, Ana (Farmacevtski vestnik, 2018)
A cross-sectional study in Slovenian community pharmacies included 292 patients of which 77% had asthma, 16% had COPD, and 6% had asthma and COPD. Majority of patients (70%) had incorrect inhalation technique. The most frequent errors were observed in the incorrect preparation of the inhaler, failure to exhale prior inhalation and inappropriate inhalation. Approximately a quarter (23%) of patients with asthma and/or COPD had low medication adherence. In 38% of patients with asthma the disease was not controlled and in 31% of patients with COPD the disease had a high or very high impact on their life. Disease control and quality of life were especially poor in patients with asthma and COPD. Over a period of one year, 25% of patients with asthma and/or COPD experienced acute exacerbation of the disease. Medication adherence in patients with asthma influenced disease control and quality of life. However, we did not manage to show that in patients with COPD.
Keywords: Astma; bolniki z astmo; kakovost življenja; Kronična obstruktivna pljučna bolezen; nadzor bolezni; zdravljenje z zdravili